Penerapan Perilaku Hidup Bersih dan Sehat (PHBS) Dalam Pencegahan Kecacingan Pada Siswa SD Negeri Pampang Kecamatan Panakkukang Kota Makassar - Indraswari, Ni Luh Astri; Haderiah, Haderiah; Tiku, Marjeni (Sulolipu: Media Komunikasi Sivitas Akademika dan Masyarakat, 2024)
Soil-transmitted helminth (STH) infection is a disease caused by lack of clean and healthy living habits implementation. School-aged children contribute the highest prevalence rate to STH infections. The highest area of ​​STH cases in Makassar is at Pampang Health Center working area. This research aims to describe the knowledge, attitudes and actions of Pampang State Elementary School students regarding the implementation of clean and healthy living habits. The type of research was descriptive observational using questionnaires. Respondents are 130 students from grade 5 and grade 6 at Pampang State Elementary School. An overview of students' STH infection conditions was obtained through a sample test by taking 5 fecal samples among respondents using simple random sampling. Samples examined microscopically to see the presence of worm eggs in the feces. The research results showed that 122 students (93.84%) had a high level of knowledge regarding clean and healthy living habits. There were 102 students (78.47%) who had good attitudes towards PHBS and 124 students’ actions were good (95.39%). The results of fecal samples examination showed that 4 samples were positively infected by Ascaries lumbricoides. Even though students already have good knowledge, attitudes and actions regarding clean and healthy living habits, this doesn’t mean they are free from STH infection. It is recommended that school and community health center monitor the students’ clean and healthy living habits implementation.  Key words: Soil-transmitted helminth infection; clean and healthy living habits; school-aged children